Verification of model simulated mass balance, flow fields and tabular calving events of the Antarctic ice sheet against remotely sensed observations - Ren, Diandong; Leslie, L.; Lynch, Mervyn (Springer, 2013)
The Antarctic ice sheet (AIS) has the greatestpotential for global sea level rise. This study simulates AISice creeping, sliding, tabular calving, and estimates the totalmass balances, using a recently developed, advanced icedynamics model, known as SEGMENT-Ice. SEGMENTIceis written in a spherical Earth coordinate system.Because the AIS contains the South Pole, a projectiontransfer is performed to displace the pole outside of thesimulation domain. The AIS also has complex ice-watergranularmaterial-bedrock configurations, requiringsophisticated lateral and basal boundary conditions.Because of the prevalence of ice shelves, a ‘girder yield’type calving scheme is activated. The simulations of presentsurface ice flow velocities compare favorably with InSARmeasurements, for various ice-water-bedrock configurations.The estimated ice mass loss rate during 2003–2009agrees with GRACE measurements and provides morespatial details not represented by the latter. The modelestimated calving frequencies of the peripheral ice shelvesfrom 1996 (roughly when the 5-km digital elevation andthickness data for the shelves were collected) to 2009compare well with archived scatterometer images. SEGMENT-Ice’s unique, non-local systematic calving schemeis found to be relevant for tabular calving. However, theexact timing of calving and of iceberg sizes cannot besimulated accurately at present. A projection of the futuremass change of the AIS is made, with SEGMENT-Iceforced by atmospheric conditions from three differentcoupled general circulation models. The entire AIS is estimatedto be losing mass steadily at a rate of*120 km3/a atpresent and this rate possibly may double by year 2100.